Broadband wireless access based on WiMAX techconology with business analysis - Siddiqui, Md. Mehedi Alam; Mithu, Mehedi Hasan (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.